Approximations to the determination of functional homology between AtPATL3 and MePATL3 via phenotype complementation (2025)
Cassava bacterial blight (CBB) is a systemic bacterial infection caused by Xanthomonas phaseoli pv. manihotis (Xpm). XopAE is a highly conserved effector among the virulence arsenal of Xpm, and elucidating what molecules it targets in cassava will provide not just a better understanding of the molecular mechanisms Xpm uses for infection but also may allow for future investigation and development of a Xpm-resistant cassava. A previously suggested target of this effector in cassava is a protein from a family called “patellins”. This protein is homologous to PATL3 from Arabidopsis thaliana, which suggests this homologue may also serve as a target for XopAE. In this project, the Arabidopsis thaliana – Pseudomonas fluorescens heterologous system was approached via characterization of two insertional knock-out lines of A. thaliana for the PATL3 gene, as well as development of the plant sable transformation construct Agrobacterium tumefaciens GV3101 (pMP90) (pBAV139: MePATL3) and generation of a vector pGEM-T Easy with AtPATL3; all of which facilitate future approximations for phenotype complementation in A. thaliana to elucidate functional homology between the patellins from A. thaliana and cassava.